2021
DOI: 10.1016/j.eclinm.2021.100851
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remote prenatal education on program participation and breastfeeding of women in rural and remote Indigenous communities

Abstract: Background: First Nations (FN) women have a higher risk of diabetes than non-FN women in Canada. Prenatal education and breastfeeding may reduce the risk of diabetes in mothers and offspring. The rates of breastfeeding initiation and participation in the prenatal program are low in FN communities. Methods: A prenatal educational website, social media-assisted prenatal chat groups and community support teams were developed in three rural or remote FN communities in Manitoba. The rates of participation of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 24 publications
0
22
1
5
Order By: Relevance
“…Midwifery care for a woman during the phase (pregnant, childbirth, and postnatal) greatly determines the quality of women's health (Hui et al, 2021). Distance prenatal education program is helpful for prenatal programs during the COVID-19 pandemic.…”
Section: The Role Of Midwives In Providing Nutrition Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Midwifery care for a woman during the phase (pregnant, childbirth, and postnatal) greatly determines the quality of women's health (Hui et al, 2021). Distance prenatal education program is helpful for prenatal programs during the COVID-19 pandemic.…”
Section: The Role Of Midwives In Providing Nutrition Educationmentioning
confidence: 99%
“…Information technology is a facility and infrastructure (hardware, software, user) system and methods to obtain, transmit, process, interpret, store, organize, and use data meaningfully. Information technology is the result of human engineering in delivering information from sender to recipient so that the transmission of information will be faster and longer (Hui et al, 2021).…”
Section: Online Pregnancy Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that remote prenatal education is effective for increasing breastfeeding rates and participation in prenatal programs in remote and rural areas. The remote education remained active during the COVID-19 pandemic, suggesting that remote educational programs can be expanded to similar locations (18). Web-based prenatal and antenatal education classes are an appropriate response to the need to offer support to pregnant women during the COVID-19 pandemic (19).…”
Section: Dear Editormentioning
confidence: 99%